Utility of polysomnography and video swallow studies in the management of pediatric patients with congenital idiopathic bilateral vocal fold dysfunction. (November 2020) - Ruda, James; Pinto, Swaroop; Allarakhia, Zahir
Abstract: Objectives: Congenital idiopathic bilateral vocal fold dysfunction (BVFD) is an uncommon cause of neonatal stridor and respiratory distress postnatally. Approximately 50% of affected neonates or infants will historically require tracheostomy for this condition. Timing and candidacy for tracheostomy in BVFD patients is often subjective and poorly understood. Polysomnography (PSG) and video swallow studies (VSS) may be helpful in the management of patients with BVFD prior to tracheostomy by quantifying their degree of upper airway obstruction during sleep and feeding dysfunction while awake. Methods: We performed a single-institution retrospective case series of BVFD patients from 2000 to 2018 who had postnatal PSGs performed prior to tracheostomy. Demographics, gestational age, and VSS results prior to PSG were recorded for all patients. Findings from PSGs included non-REM AHI, REM AHI, oxygen nadir, % total sleep time (TST) O2<90%, peak end-tidal (ET) CO2, % TST ETCO2 >52 torr. Rates of post-PSG tracheostomy, gastrostomy tube (G-tube) placement, and home O2 supplementation were noted for all patients. Results: From 2000 to 2018, 12/46 (26%) BVFD patients had postnatal PSGs performed prior to tracheostomy. Median patient age at BVFD diagnosis, VSS, and PSG was 5.5 days, 12.5 days, and 17.5 days, respectively. Mild, moderate, and severe obstructive sleep apnea (OSA) was found in 7/12, 3/12, and 4/12 patients, respectively. Hypercapnia (ETCO2 >52 torr) was found in 5/12 patients on PSG while hypoxemia (SpO2 <90% for >4% TST) was not found in any patient. VSS results demonstrated normal swallowing, inconsistent laryngeal penetration, and silent aspiration in 7/12, 2/12, and 3/12 patients, respectively. Tracheostomy and G-tube placement was performed in 3/12 and 2/12 patients, respectively. There was no association between the severity of OSA or any PSG abnormality, VSS findings, and the performance of tracheostomy in any BVFD patient. Conclusions: OSA was found in all BVFD patients undergoing postnatal PSG at our institution while feeding dysfunction was found in approximately 50% of patients. The presence of feeding dysfunction, severe OSA, or any PSG abnormality was not individually associated with the subsequent performance of a tracheostomy in our patients. PSG is likely useful in supporting but not supplanting one's clinical decision-making in the management of patients with congenital idiopathic BVFD.